Adomian Decomposition Method of Fredholm Integral Equation of the Second kind Using Maple (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we will be find exact solution of Fredholm Integral equation of the second kind through using Adomian Decomposition Method by using Maple 17 program, then we found that exact solution.